Operations management with student dvd and power web - Stevenson, William J. (New York McGraw-Hill/Irwin, 2006)
Stevenson$1 (Bs Operations Management surveys the field of operations in both services and manufacturing. As always, this new edition offers complete, balanced, and flexible coverage of operations management. With hands-on examples and support in the text, and the most extensive technology support package available, students will have a practical, deep, up to date, and motivating study resource. Combine that with the clear explanations of topics, and the countless presentation enhancements, this new Eighth Edition is the best ever. Coverage flows from the overall strategic issues of designing products and services and making major capacity and location decisions, through the operating processes and control systems, including well supported quantitative applications. Many specialty topics and quantitative techniques are segmented as supplements that can be highlighted or bypassed depending on your course structure. Topics are also supported with step-by-step examples and solved problems, many including example solutions built into Excel spreadsheetss
Keywords: management